2014
DOI: 10.1016/j.wasman.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Application of an early warning indicator and CaO to maximize the time–space-yield of an completely mixed waste digester using rape seed oil as co-substrate

Abstract: Originally published as:Kleyböcker, A., Lienen, T., Liebrich, M., Kasina, M., Kraume, M., Würdemann, H. (2014): Application of an early warning indicator and CaO to maximize the time-space-yield of a completely mixed waste digester using rape seed oil as co-substrate. AbstractIn order to increase the organic loading rate (OLR) and hereby the performance of biogas plants an early warning indicator (EWI-VFA/Ca) was applied in a laboratory-scale biogas digester to control process stability and to steer additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It was understandable that low concentration of LCFA resulted from crystallizing with calcium, while the similar profile of LCFAs in TR was probably due to the LCFA having been degraded to VFA which was reflected in the accumulation of acetate and propionate (Table S1), and ultimately contributed to the process setup. Kleyböcker et al (2014) also reported that the thermophilic AD of organic wastes could be promoted without VFA accumulation by adding calcium oxide. The crystallization mechanism of calcium salts with LCFA was surely related to the temperature but more likely to be influenced by the acidity, ion varieties and strength, mass transfer, and other factors deduced from the digestion temperature, which needs further research.…”
Section: Resultsmentioning
confidence: 95%
“…It was understandable that low concentration of LCFA resulted from crystallizing with calcium, while the similar profile of LCFAs in TR was probably due to the LCFA having been degraded to VFA which was reflected in the accumulation of acetate and propionate (Table S1), and ultimately contributed to the process setup. Kleyböcker et al (2014) also reported that the thermophilic AD of organic wastes could be promoted without VFA accumulation by adding calcium oxide. The crystallization mechanism of calcium salts with LCFA was surely related to the temperature but more likely to be influenced by the acidity, ion varieties and strength, mass transfer, and other factors deduced from the digestion temperature, which needs further research.…”
Section: Resultsmentioning
confidence: 95%
“…This point suggests that this organism lowered the hydrogen partial pressure in the granules, allowing the degradation of VFAs. Kleyböcker et al [ 3 ] also found relatives of Methanoculleus and Methanosarcina dominating a high-performance biogas formation process stabilized by aggregate formation. Thus, the granules provide microhabitats with favorable conditions, even though the conditions in the digestate are unfavorable.…”
Section: Resultsmentioning
confidence: 99%
“…For testing purposes, the process was operated with the same substrates and calcium oxide (CaO) as an additive at a high OLR of 9.5 kg volatile solids (VS)·m −3 ·d −1 . Phosphate-accumulating organisms (PAOs) such as Dechloromonas - and Rhodocyclales -like bacteria were present and may have contributed to maintaining a stable the process [ 3 ]. In addition, Kleyböcker et al [ 4 ] showed that phosphate and the ratio of volatile fatty acids (VFAs) to calcium had an early warning function in terms of over-acidification.…”
Section: Introductionmentioning
confidence: 99%
“…Under an overloading condition, excessive organic acids can accumulate in the system. Both methanogenic population and the Syntrophomonadaceae family, which has been identified with the syntrophic relationship to methanogenic Archaea, decreased significantly due to the accumulation of volatile fatty acids (Kleyböcker et al, 2014;Regueiro et al, 2015). Hence, a retention time much longer than the period of 48 days in this study would be required to evaluate the specific methane yield (Holliger et al, 2016).…”
Section: Effects Of Organic Loading On Specific Methane Yieldsmentioning
confidence: 97%